The synergistic relationship between Amartya Sen entitlement theory and the systems theory in developing a food security implementation model in Matabeleland South Province, Zimbabwe - Muzerengi, Tapiwa (Jamba, 2021)
Food insecurity has increasingly become a topical issue that needs to be addressed before it goes out of hand. The article explores the synergistic relationship that exists between Amartya Sen entitlement and systems theories. The article hypothesises that food insecurity in Matabeleland South Province is mainly caused by a lack of understanding of food security pillars and how all the concepts dove tail into the food security discourse. The article further propounds that, for communities to go out of the food insecurity quagmire, they need to work collaboratively as a system as substantiated by the systems theory. Sen argues that the law stands between food availability and access. This is further simplified as follows: food can be available in the markets but the people might lack the purchasing power to purchase the food. When people try to acquire food through stealing, the law catches on them. On the other hand, the systems theory argues that for a community to function well all the parts should play their roles towards the survival of the whole. The theory further informs that government stakeholders and non-state actors must work together in addressing food insecurity without a clearly defined direction. Interactions with provincial stakeholders, revealed that, a leaf can be borrowed and applied from the two theoretical models to achieve food security in Matabeleland South Province in Zimbabwe.